High performance Ni catalysts prepared by freeze drying for efficient dry reforming of methane - Huang, Jijiang (2020)
For supported metal catalysts, the architectures of the supports are as important as the chemical compositions of the catalysts and the morphologies of the supported metal particles. In this work, we report a simple and versatile method for preparing Ni nanoparticle catalysts supported on Mg-Al mixed oxides for the dry reforming of methane. The catalysts were prepared by freeze drying of Ni-Mg-Al layered double hydroxide precursors, followed by calcination and H2 reduction. Compared to Ni/Mg-Al-O catalysts prepared by oven drying, the freeze-dried catalysts retain a unique, loosely packed platelet structure with high macroporosity, which gives rise to high dispersion, high DRM activity and high resistance against deactivation. At 800 °C, the catalyst consistently achieves equilibrium CH4 conversion of 95% over 100 h time on stream with a of 40 L-CH4 h−1 g-cat−1. The DRM activity seen in the present study supersedes other Ni-based catalysts reported in the literature.